2000
DOI: 10.1128/mcb.20.21.7881-7892.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Yeast, the 3′ Untranslated Region or the Presequence of ATM1 Is Required for the Exclusive Localization of Its mRNA to the Vicinity of Mitochondria

Abstract: We isolated mitochondria from Saccharomyces cerevisiae to selectively study polysomes bound to the mitochondrial surface. The distribution of several mRNAs coding for mitochondrial proteins was examined in free and mitochondrion-bound polysomes. Some mRNAs exclusively localize to mitochondrion-bound polysomes, such as the ones coding for Atm1p, Cox10p, Tim44p, Atp2p, and Cot1p. In contrast, mRNAs encoding Cox6p, Cox5a, Aac1p, and Mir1p are found enriched in free cytoplasmic polysome fractions. Aac1p and Mir1p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 57 publications
5
137
0
1
Order By: Relevance
“…Almost half the studied mRNAs from nuclear genes encoding mitochondrial products were found to be translated in the vicinity of mitochondria. This confirms and considerably extends previous observations based on a limited number of genes (Ades and Butow, 1980;Suissa and Schatz, 1982;Corral-Debrinski et al, 2000). It has already been shown that such genomic-wide approaches can produce crucial information concerning transcripts known to encode secreted or membrane proteins present in large amounts in membrane-bound fractions (Diehn et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Almost half the studied mRNAs from nuclear genes encoding mitochondrial products were found to be translated in the vicinity of mitochondria. This confirms and considerably extends previous observations based on a limited number of genes (Ades and Butow, 1980;Suissa and Schatz, 1982;Corral-Debrinski et al, 2000). It has already been shown that such genomic-wide approaches can produce crucial information concerning transcripts known to encode secreted or membrane proteins present in large amounts in membrane-bound fractions (Diehn et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…We showed previously, when studying the ATM1mRNA (Corral-Debrinski et al, 2000), that the 3′-UTR contains sufficient information to target RNA to the vicinity of mitochondria. Therefore, we investigated the in vivo RNA targeting properties of eight 3'-UTRs from mRNAs that were found to be in close vicinity to mitochondria (MLR from 84 to 98).…”
Section: In Vivo Localization Of Mrnas Of High Mlr Valuementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that many mRNAs and RNA-binding proteins are localized to specific compartments, along with cytoskeletal elements, in a variety of eukaryotic cells (Jansen, 2001;Kloc et al, 2002). In S. cerevisiae, many mRNAs are localized to produce proteins in specific compartments such as the daughter cell or the mitochondria (Corral-Debrinski et al, 2000;Takizawa et al, 2000;Jansen, 2001;Kwon and Schnapp, 2001;Shepard et al, 2003). These observations suggest that individual mRNAs may be consistently transported to specific areas in the yeast cell.…”
Section: Discussionmentioning
confidence: 95%
“…Genes of ancient bacterial origin comprise a significant proportion of these mitochondrion-associated mRNAs, while genes of eukaryotic origin that encode organellar proteins generally contain presequences and seem to be primarily translated on cytoplasmic polysomes [50]. The ribosomal recruitment of mRNAs requires specific features of the 3′ untranslated region of the transcripts [51]. mRNA segregation as an alternative, co-translational route for organellar protein import has only been described in mammalian and fungal cells to date, but it seems likely that such a system will be found in plant cells as well.…”
Section: Acknowledgmentsmentioning
confidence: 99%